Neuropsychological functioning and jumping to conclusions in delusions. - Garety, P; Joyce, E; Jolley, S; Emsley, R; Waller, H; Kuipers, E; Bebbington, P; Fowler, D; Dunn, G; Freeman, D (2013)
BACKGROUND: It has been consistently demonstrated that delusions are related to jumping to conclusions (JTC), a data-gathering bias and potential candidate endophenotype of psychosis. Recent research suggests that JTC may be a marker of treatment response. However, we know little about the factors contributing to the occurrence of this reasoning bias. This study investigated the relationship between JTC and hypothesised deficits in working memory, employing standard well-validated neuropsychological tests, in people with current delusions. METHOD: One hundred and twenty six people with schizophrenia spectrum psychosis and current delusions were assessed for current symptoms, and tested for JTC. We compared performance on tests of working memory in those with the reasoning bias and those without. RESULTS: As expected, 30-40% of this sample of people with current delusions showed the JTC bias. There were no differences in premorbid IQ between those with and without the JTC reasoning bias. However, the performance of the JTC group was significantly worse on tests of working memory. CONCLUSIONS: The JTC data-gathering bias is associated with impairments in working memory. New non-pharmacological interventions for people with delusions, designed to improve data gathering, may benefit from incorporating strategies to overcome deficits in working memory.